Correlation between the Expression of Melanoma-Associated Antigen-A3 and Cytology Results on Bronchoalveolar Lavage on Nsclc - Mawartih Susanty1,Isinin Anang Marhanang2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Lung cancer is still considered an alarming health problem, causing a major cause of death in malignant disease. The incidence rate is likely to increase and most of it comes with an advanced stage of diagnosis. To improve the healing rate and life expectancy, the detection of lung cancer should be done early, when it is still small and localized. Bronchoalveolar lavage (BAL) cytology is a method of examination that can be used in lung cancer. The expression of Melanoma-Associated Antigen (MAGE) becomes the marker that is sensitive to certain types of cancer, including lung cancer. Objective:To analyze the correlation between expression MAGE-A3 and cytology of BAL specimen on NSCLC. Method: Bronchoscopy was performed on patients with NSCLC lung tumor at pulmonology unit of Dr. Soetomo Teaching Hospital Surabaya Indonesia to collect the BAL. Histologic examination for BAL and MAGE-A3 examination were conducted on patients. Statistical analysis used to determine the correlation between the expression of MAGE A3 and cytology of BAL specimens on NSCLC was fisher’s exact test. Result: We found that there were 7.14% of subjects with BAL cytology had cancer cells (adenocarcinoma). MAGE-A3 expression was positive only in 28.60% of subjects diagnosed with NSCLC. The result of MAGE A3 expression analysis with cytology of BAL specimen showed p = 0.286. Conclusion: There was no significant correlation between MAGE-A3 expression and histopathology type. The results of MAGE A3 RT PCR fluid expression examination showed that most of them were in the negative category.